TANTANGAN PENDIDIKAN VOKASIONAL BERBASIS OUTCOME DALAM KURSUS ONLINETERBUKA MASIF: TINJAUAN PERSPEKTIF KURIKULUM - Nur Wahyuni (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2023)
Digitalization in the Industrial 4.0 era has changed the order and process of education, one of which is the presence of Massive Open Online Courses (MOOC). This article reviews the challenges of implementing MOOCs in Vocational Education (PV). Several literature sources, including books and journals, were compiled and engaged in literary analysis in this writing. The analysis results identified five significant challenges that arise during the implementation of MOOCs in PV. These challenges include student competency achievements, infrastructure adequacy, psychological condition, engagement, and evaluation and assessment. In the case of Indonesia itself, the MOOC challenge has not been followed up properly, so the impact related to the outcome still cannot be increased. The results in this paper give an important signal, especially for PV organizers, to play an essential role in responding to these challenges. The primary keys are to develop teacher competencies and prepare the excellent vocational infrastructure for implementing MOOCs in PV. In addition, curriculum improvements to boost achievements in MOOCs are also the main foundation that must be strengthened. Further research is also expected to play an essential role in developing the critical sectors involved in the success of MOOCs in PV